EFFECTIVENESS OF BOTANICAL BIOPESTICIDES WITH DIFFERENT CONCENTRATIONS OF TERMITE MORTALITY - Cornelia M.A. Wattimena; Fransina Sarah Latumahina (Forestry Study Program University Of Mataram, 2021)
The aim of this study was to determine the effect of botanical biopesticide extracts and concentrations on soil termite mortality of Coptotermes curvignathus, Holmgren. This research was an experimental study using a fully randomized design (CRD) consisting of 2 3-level treatments that were repeated three times. Treatment was a type of botanical biopesticide consisting of three levels, namely are A1 (papaya leaf), A2 (soursop leaf), A3 (lemongrass leaf). In comparison, the concentration of botanical biopesticide consists of three levels: B0 (without or as a control biopesticide), B1 (500 grams), B2 (1,000 grams) and B3 (1,500 grams) which have been repeated three times. The data that had been tabulated was then analyzed using Variant Analysis, and if there was any influence, the difference test was continued at 5 % and %. The results showed that the treatment of papaya leaf biopesticides (A1) had a faster reaction to the death rate of termite (95.6 % ) and the lowest was the death rate of soursop leaf (A2) termite (90.7 % ). In comparison, lemongrass (A3) caused soil termite mortality (94.1 %). In addition , treatment of biopesticide concentrations of B3 (1,500 grams) resulted in higher termite mortality of 96.67 %. compared to B2 (1,000 grams) with mortality of 94.07 % and B1 (500 grams) with mortality of 89.62 %.Whereas, for the interaction between the two treatments, the highest level of termite mortality was papaya leaf biopesticide with a concentration of 1,500 grams (A1B3) and termite mortality was 100 %.